Financial inclusion and women participation in gainful employment: an empirical analysis of Nigeria - Musa Abdullahi Sakanko (Fakultas Ekonomi dan Bisnis Islam, Institut Agama Islam Negeri (IAIN) Salatiga, 2020)
The paper examines the effect of financial inclusion on women participation in gainful employment in Nigeria for the period 1980 – 2018, employing the ARDL method. Both in the short run, and long-run the results obtained indicated a positive relationship between financial inclusion and women participation in gainful employment. Thus, the paper recommends that the government should ensure that the barriers to financial inclusion is reduced or removed. This will increase women participation in economic activities, since measures regarding financial inclusion is adjudged as convenient, safety and prompt. Measures that will enhance private deposit and expansion of more commercials banks branch in rural areas to enhance women’s access to financial services which discourage the use of informal financial services should be encouraged.